2012
DOI: 10.1051/epjconf/20122900034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chitosan gel

Abstract: Abstract. Aerogel conditioning of the chitosan makes it possible to prepare porous solids of significant specific surface. The increase in the chitosan concentration or the degree of acetylation decreases the specific surface of the synthesized chitosan gel. Whereas drying with supercritical CO 2 more effectively makes it possible to preserve the volume of the spheres of gel and to have a more significant specific surface in comparison with evaporative drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The PECs produced at the higher pH range (pH 9-12), contained approximately 30% more CS than PECs produced at the lower pH range (pH 3-8). The moisture contents of PECs prepared at higher pHs (range 9-12) were approximately eight times larger than the moisture contents present in PECs prepared at lower pH range (3)(4)(5)(6)(7). The FTIR spectra were used to confirm the electrostatic interaction during PEC formation ( figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PECs produced at the higher pH range (pH 9-12), contained approximately 30% more CS than PECs produced at the lower pH range (pH 3-8). The moisture contents of PECs prepared at higher pHs (range 9-12) were approximately eight times larger than the moisture contents present in PECs prepared at lower pH range (3)(4)(5)(6)(7). The FTIR spectra were used to confirm the electrostatic interaction during PEC formation ( figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
“…The low costs are due to the abundance of waste shrimp shells and farmed red seaweed and their relatively simple extraction methods [4]. CS, a positively-charged polysaccharide is widely considered as the second most abundant organic material after cellulose [5]. CS possesses appealing intrinsic properties such as being biodegradable [6] and bacteriostatic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported ambient/ vacuum-drying of chitosan xerogels,but only as acomparative method to supercritical or freeze-drying,a nd most of the resulting materials had low surface areas. [111,180] 3. Process-Structure-Property Relations Tables S1-S5 provide an overview of the physical properties (density,p orosity,s pecific surface area, pore volume, compression elastic modulus) and categories of microstructure from SEM images (macroporous/mesoporous,c ellular/ fibrous/particulate) of chitosan aerogels reported in the literature.I nt his section, we extract general trends between processing (gelation, drying) and structural properties for pure chitosan systems (Table S1).…”
Section: Evaporative Dryingmentioning
confidence: 99%
“…Einige Studien beschrieben die Umgebungs-/Vakuumtrocknung von Chitosan-Xerogelen, allerdings lediglich als ein Vergleichsverfahren zur überkritischen Trocknung oder Gefriertrocknung,u nd die meisten der resultierenden Materialien zeigten kleine Oberflächen. [111,180]…”
Section: Verdunstungstrocknungunclassified